2013
DOI: 10.1007/s12663-013-0557-9
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a Single Dose Intravenous Paracetamol for Pain Relief After Maxillofacial Surgery: A Randomized Clinical Trial Study

Abstract: Paracetamol is effective on pain relief after maxillofacial surgeries. Operation time may be an important factor for induction of pain after the surgeries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 24 publications
(27 reference statements)
0
3
0
1
Order By: Relevance
“…Furthermore, patients who underwent mandibular surgery reported higher pain and required more analgesic drugs than those who underwent only maxillary surgery [ 23 ]. A single dose of intravenous paracetamol could relief the pain after surgery for mandibular fractures [ 19 ]. It has been reported that there was a similar efficacy between a single dose of 1 g intravenous paracetamol and 75 mg intramuscular diclofenac sodium in postoperative pain control for orthognathic surgery [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, patients who underwent mandibular surgery reported higher pain and required more analgesic drugs than those who underwent only maxillary surgery [ 23 ]. A single dose of intravenous paracetamol could relief the pain after surgery for mandibular fractures [ 19 ]. It has been reported that there was a similar efficacy between a single dose of 1 g intravenous paracetamol and 75 mg intramuscular diclofenac sodium in postoperative pain control for orthognathic surgery [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…The sample size was calculated using the formula for a randomized controlled trial [ 22 ] based on the visual analogue scale pain intensity from a previous study [ 19 ] (mean in the treatment group = 3.98, SD. in the treatment group = 0.69, mean in the control group = 4.63, SD.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Parasetamol memiliki kelebihan dibandingkan Non-steroidal anti-inflammatory drugs (NSAID) karena NSAID konvensional dapat berkaitan dengan efek serius yang tidak diinginkan seperti perdarahan atau gangguan pada ginjal apabila digunakan sebelum tindakan operasi. 17 Parasetamol intravena merupakan obat pereda nyeri yang efektif dalam mengontrol rasa sakit saat keadaan darurat juga pasca operasi. 18 Tindakan operasi dilakukan dalam anestesi umum.…”
Section: Pembahasanunclassified